Vitamin E-grafted crosslinked ultrahigh-molecular weight polyethylene (VE-HXPE) inhibits fluid absorption and has long term oxidative stability. (December 2015) - Popoola, Oludele O.; Mimnaugh, Kimberly; Orozco-villasenor, Diego A.; Peiserich, Melinda
Abstract: Oxidation of in vivo -absorbed lipids such as squalene and cholesterol may limit the life of melted or annealed crosslinked polyethylene (HXPE) implants. Combining vitamin E with HXPE (VE-HXPE) increases the oxidation resistance of HXPE. This study investigates the fluid absorption characteristics and long-term oxidative stability of VE-HXPE and HXPE implants. VE-HXPE and HXPE cubes were soaked in squalene at 37 ± 2 °C and compressively loaded at 500/50 N (R = 0.1) for 500 h and time dependence of squalene absorption was determined. Additionally, serum lubricant absorbed by 40 mm HXPE and VE-HXPE acetabular components during a 45 million cycle (Mc) hip wear test was gravimetrically determined. HXPE and VE-HXPE ASTM type V dog bones were aged at 70 °C under 0.482 MPa of 100% oxygen for up to 33 weeks and the oxidation index was determined using FTIR. The HXPE and VE-HXPE acetabular components absorbed 126.3 ± 49.0 mg and 33.1 ± 6.7 mg of bovine serum respectively during the 45 Mc wear test. FTIR measured OI ≤ 0.05 for VE-HXPE and OI = 2.05 ± 1.48 for HXPE after 33 weeks and 4 weeks of aging respectively. The results are explained in terms of differences in crystallinity and chemistry of the amorphous phase in blended VE-HXPE.